The interference of alcohol consumption in the effectiveness of pharmacotherapy with antibiotics (Research, Society and Development, 2023)
Introduction: The use of medicines has become routine in the lives of the population, but what worries the healthcare team most is the use of these medicines, especially antibiotics associated with alcohol, which can generate unwanted consequences to this treatment. Objective: Raise awareness about the risks of combining alcohol and medication. Methods: This is a qualitative research on the effects of alcohol in pharmacotherapy with antibiotics (2018-2023). Narrative review, interpretative data analysis, identification of patterns and trends, providing insights for safer pharmacotherapy. Emphasis on practices and awareness of risks for health professionals and the population. Results: Consumption of alcohol in combination with some medications, such as antibiotics, can have harmful effects and alter the effectiveness of treatment. This can result in lower levels of the medicine in the blood, compromising its effectiveness in fighting infection. In more serious cases, the interaction between alcohol and safe antibiotics can lead to dangerous reactions, making it essential to avoid alcohol consumption during treatment with these medications. It is important to emphasize that the use of antibiotics must be done under prescription, following the instructions of the healthcare professional. Conclusion: It is concluded that it is essential to avoid alcohol consumption during antibiotic treatment to ensure the effectiveness and safety of the treatment.